PENGARUH MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN (STUDI KASUS PADA KARYAWAN OBAMA MARKET BIREUEN) - Putri Khairani; Lisa Iryani (Negotium: Jurnal Ilmu Administrasi Bisnis, 2021)
This study aims to determine (1) the effect of work motivation on the performance of Obama Market Bireuen employees (2) the effect of the work environment on Obama MArke Bireuen employees, (3) The effect of work motivation and work environment on Obama Market Bireuen employee performance. This research is a causal associative reaserch using a quantitative approach. This research is categorized as a survey research, where the research, instrument are interviews and questionnaires. The sample in this study is a saturated sample by taking the entire population of employees at Obama Market Bireuen, amounting to 20 people. The validity test of the instrument used Confirmatory Factor Analysis (CFA), the reability test used Cronbach Alpha, while data analysis was performed using multiple linear regression analysis with the help os SPSS softwere. The result showed that (1) work motivation has a positive affaect on employee performance at the Obama Market Bireuen 1.088. The contribution of work motivation to explain employee performance is 0,768. (2) The work environment ha a positive effect on employee performance Obama Market Bireuen  0.296. The contribution of work environment to explain employee performance is a 0,301. (3) Work motivation and work environment together have a positive effect on Obama Market Bireuen employee performance by 0.894 or 89.4% and the remaining 10.6% is influenced by other variables.